Microscale Self-Assembly of Upconversion Nanoparticles Driven by Block Copolymer - Su, Qianqian; Zhou, Meng-Tao; Zhou, Ming-Zhu; Sun, Qiang; Ai, Taotao; Su, Yan (Frontiers in Chemistry, 2020)
Lanthanide-based upconversion nanoparticles can convert low-energy excitation to high-energy emission. The self-assembled upconversion nanoparticles with unique structures have considerable promise in sensors and optical devices due to intriguing properties. However, the assembly of isotropic nanocrystals into anisotropic structures is a fundamental challenge caused by the difficulty in controlling interparticle interactions. Herein, we report a novel approach for the preparation of the chain-like assemblies of upconversion nanoparticles at different scales from nano-scale to micro-scale. The anisotropy of chain-like assembly can be ﬁne-tuned using various incubation times. Our study observed Y-junction aggregate morphology due to the flexible nature of amphiphilic block copolymer. Furthermore, the prepared nanoparticle assemblies of upconversion nanoparticles with lengths up to several micrometers can serve as novel luminescent nanostructure and offer great opportunities in the fields of optical applications.